Efficiency of dihydroxamic and trihydroxamic siderochelates to extract uranium and plutonium from contaminated soils. (September 2021) - Février, Laureline; Coppin, Frédéric; Pierrisnard, Sylvie; Bourdillon, Mélanie; Nguyen, Lé Vi; Zaiter, Nissrine; Brandès, Stéphane; Sladkov, Vladimir; Chambron, Jean-Claude; Meyer, Michel
Abstract: Actinide-based mineral phases occurring in contaminated soils can be solubilized by organic chelators excreted by plants, such as citrate. Herein, the efficiency of citrate towards U and Pu extraction is compared to that of siderophores, whose primary function is the acquisition of iron(III) as an essential nutrient and growth factor for many soil microorganisms. To that end, we selected desferrioxamine B (DFB) as an emblematic bacterial trishydroxamic siderophore and a synthetic analog, abbreviated (L Cy, Pr )H2, of the tetradentate rhodotorulic acid (RA) produced by yeasts. Firstly, the uranyl speciation with both ligands was assessed in the pH range 2–11 by potentiometry and visible absorption spectrophotometry. Equilibrium constants and absorption spectra for three [UO2 (DFB)H h ] ( h −1)+ ( h  = 1–3) and five [UO2 (L Cy, Pr ) l H h ] (2+ h −2 l )+ (−1 ≤  h  ≤ 1 for l  = 1 and h  = 0–1 for l  = 2) solution complexes were determined at 25.0 °C and I  = 0.1 M KNO3 . Similar studies for the Fe 3+ /(L Cy, Pr ) 2– system revealed the formation of five species having [Fe(L Cy, Pr )] +, [Fe(L Cy, Pr )OH], [Fe(L Cy, Pr )(OH)2 ] –, [Fe(L Cy, Pr )2 H], and [Fe2 (L Cy, Pr )3 ] compositions. Then, the ability of DFB, (L Cy, Pr )H2, and citrate to solubilize either U or Pu from pitchblende-rich soils (soils 1 and 2) or freshly plutonium-contaminated soils (LBS and PG) was evaluated by performing batch extraction tests. U was extracted significantly only by citrate after a day. After one week, the amount of U complexed by citrate only slightly exceeded that measured for the siderochelates, following the order citrate > (L Cy, Pr )H2  ≥ DFB ≈ H2 O, and were comparatively very low. Pu was also more efficiently extracted by citrate than by DFB after a day, but only by a factor of ~2–3 for the PG soil, while the Pu concentration in the supernatant after one week was approximately the same for both natural chelators. It remained nearly constant for DFB between the 1st and 7th day, but drastically decreased in the case of citrate, suggesting chemical decomposition in the latter case. For the Fe-rich soils 1 and 2, the efficiencies of the three chelators to solubilize Fe after a day were of the same order of magnitude, decreasing in the order DFB > citrate > (L Cy, Pr )H2 . However, after a week DFB had extracted ~1.5 times more Fe, whereas the amount extracted by the other chelators stayed constant. For the less Fe-rich LBS and PG soils contaminated by Pu, the amounts of extracted Fe were higher, especially after 7 days, and the DFB outperformed citrate by a factor of nearly 3. The higher capacity of the hexadentate DFB to extract Pu in the presence of Fe and its lower ability to mobilize U qualitatively agree with the respective complexation constant ratios, keeping in mind that both Pu-containing soils had a lower iron loading. Noticeably, (L Cy, Pr )H2 has roughly the same capacity as DFB to solubilize U, but it mobilizes less Fe than the hexadentate siderophore. Similarly, citrate has the highest capacity to extract Pu, but the lowest to extract Fe. Therefore, compared to DFB, (L Cy, Pr )H2 shows a better U/Fe extraction selectivity and citrate shows a better Pu/Fe selectivity. Highlights: Pu is efficiently extracted from artificially contaminated soils by desferrioxamine B An abiotic rhodotorulic-like acid extracted more efficiently naturally occurring U in soils than desferrioxamine B due to a lower affinity for Fe After 1 day, citrate has extracted much more U and Pu from Fe-rich soils than hydroxamate siderochelates Due to degradation, the higher extractability power of citrate is lost after one week